Molecular and epidemiological analysis of a Burkholderia cepacia sepsis outbreak from a tertiary care hospital in Bangladesh. - Refath Farzana; Lim S Jones; Md Anisur Rahman; Kirsty Sands; Edward Portal; Ian Boostrom; Md Abul Kalam; Brekhna Hasan; Afifah Khan; Timothy R Walsh (Public Library of Science (PLoS), 2020)
BACKGROUND:Burkholderia cepacia complex (Bcc) is a group of serious pathogens in cystic fibrosis patients and causes life threatening infections in immunocompromised patients. Species within the Bcc are widely distributed within the environment, can survive in the presence of disinfectants and antiseptics, and are inherently multidrug resistant (MDR). METHODS:Dhaka Medical College Hospital (DMCH) patients with a B. cepacia positive blood culture between 20 October 2016 to 23rd September 2017 were considered as outbreak cases. Blood stream infections (BSIs) were detected using BacT/ALERT 3D at DMCH. B. cepacia was isolated on chromogenic UTI media followed by MALDI-TOF. Minimum inhibitory concentration (MIC) of clinically relevant antibiotics was determined by agar dilution. Whole genome sequencing was performed on an Illumina MiSeq platform. Patients' demographic and clinical data were collected. Patients' clinical history and genomic data of the outbreak strains were merged to investigate possible outbreaks. Ninety-one B. cepacia genomes were downloaded from 'Burkholderia Genome Database' and the genomic background of the global strains were compared with our outbreak strains. RESULTS:Among 236 BSIs, 6.35% (15/236) were B. cepacia. Outbreak cases were confined to the burn critical care unit and, to a lesser extent, the paediatrics department. There was a continuum of overlapping cases at DMCH between 23 October 2016 to 30 August 2017. Core genome SNPs showed that the outbreak strains were confined to a single clade, corresponded to a common clone (ST1578). The strains were shown to be MDR and associated with a mortality of 31% excluding discharge against medical advice. MIC profiles of the strains suggested that antibiotics deployed as empirical therapy were invariably inappropriate. The genetic background of the outbreak strains was very similar; however, a few variations were found regarding the presence of virulence genes. Compared to global strains from the Burkholderia Genome Database, the Bangladeshi strains were genetically distinct. CONCLUSIONS:Environmental surveillance is required to investigate the aetiology and mode of transmission of the B. cepacia outbreak. Systematic management of nosocomial outbreaks, particularly in resource limited regions, will mitigate transmission and will improve patients' outcomes.